LOKALITAS ISLAM PESISIR (Studi Kasus Aktifitas Perembus dalam Perspektif ‘Urf ‘Izzuddin bin ‘Abd al-Salam Di Desa Kaduara Barat Pamekasan Madura) - Mansur Mansur (Ulumuna: Jurnal Studi Keilsman, 2019)
Perembus activities have many roles. Starting from serving financial and capital services, fishing partners and companies, agents of socio-economic change, culture-religious and education. There is a unique triangle of relations between the perembus-jhereghen jurung in selling fish catches and the perembus-relationship relation with the provision of facilities and fees, which all have the interest to make large financial gains and seem to shift Islamic values. With a qualitative-ethnographic approach, this study will give birth to a new type of religion in the context of Islam in coastal Madura. Perembus as a company 'intermediary' with fishermen provides a strategic role whose position is parallel even above the social status of the clerics and religious teachers. For the coastal community, the perembus is orèng soghi, 'ruler' and a place to complain for oreng miskèn. Perembus activities in the local coastal ‘urf do not rely on cultural fields, sacred tombs, sacred wells and sacred mosques with the aim of "obtaining blessings", but instead focus on product-reflection in the content of coastal community awareness, especially perembus. Reflection-products grow and develop to form non-socio-cultural material in their activities as an 'intermediary' of the company with fishermen.